HOSPITAL RESPONSIBILITY FOR MEDICAL MALPRACTICE IN THE PERSPECTIVE OF INDONESIAN CRIMINAL LAW - Andi Khaedhir Kamri (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the concept and application of hospital criminal liability in cases of medical malpractice in the Indonesian criminal law system, as well as examine the relationship between the individual responsibility of medical personnel and the responsibility of hospital institutions. This study uses a qualitative approach with case study methods and a juridical-normative approach enriched with empirical data. Data was collected through in-depth interviews with legal practitioners, medical personnel, and hospital managers, accompanied by a documentary study of laws and regulations, court rulings, and related literature. The results of the study show that criminal liability in cases of medical malpractice is generally still focused on individual medical personnel as direct perpetrators, while the accountability of hospital institutions has not been optimally applied in criminal law enforcement practices. In addition, it was found that there is a complex relationship between the professional responsibilities of medical personnel and the institutional obligations of hospitals in ensuring health service standards, including aspects of supervision, risk management, and medical service systems. This study concludes that it is necessary to strengthen the concept of corporate criminal liability for hospitals in cases of medical malpractice in order to create legal certainty and more balanced protection for patients, medical personnel, and health service institutions. The findings of this study contribute to the development of health law studies and become a basis for consideration for policymakers in formulating more effective regulations and law enforcement mechanisms.